2019
DOI: 10.1103/physrevb.100.155106
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical phase diagram of unconventional alkali-doped fullerides

Abstract: By constructing an effective model based on recently calculated ab initio bare interaction parameters, we study the phase diagram of alkali doped fullerides as a function of temperature and internal pressure. We use a slave-rotor mean-field approach at the weak and intermediate coupling limits and a variational mean-field approach at the strong coupling limit, and find a good agreement with experimental phase diagram. We explain the unified description of the phase diagram including the proximity of s-wave sup… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 72 publications
(120 reference statements)
0
1
0
Order By: Relevance
“…While most variational approaches are valid only at zero temperature, the mean-field theories are unable to capture quantum fluctuations. However, slave particle theories are valid at both zero and finite temperatures and capable of capturing quantum fluctuations [44][45][46][47][48]. Further, it has been shown that slaveparticle approaches are equivalent to a statistically-consistent Gutzwiller approximation [49].…”
Section: Slave Spin Representation Of the Modelmentioning
confidence: 99%
“…While most variational approaches are valid only at zero temperature, the mean-field theories are unable to capture quantum fluctuations. However, slave particle theories are valid at both zero and finite temperatures and capable of capturing quantum fluctuations [44][45][46][47][48]. Further, it has been shown that slaveparticle approaches are equivalent to a statistically-consistent Gutzwiller approximation [49].…”
Section: Slave Spin Representation Of the Modelmentioning
confidence: 99%